Best practice of outsourcing in electrical and electronics companies in Malaysia - Hassan, Mohamad Ghozali; Razalli, Mohd Rizal; Abdul Talib, Asmat Nizam (Universiti Utara Malaysia Press, 2015)
The challenges in the business world never stop escalating as today’s customer are more difficult to satisfy, company’s products are easily copied, and technology is changing rapidly.Outsourcing is becoming more popular in today’s business as companies have limited resource to become the best in every business process.However, not all outsourcing are successful.The initial intention to save costs may result in increasing of costs if outsourcing activities are not extensively planned.The intention of this monograph is simple as the writers intend to introduce a good practice of relational-oriented exchange that will lead to better outsourcing performance.It is hope to address issues surrounding customer demand and market competition which is found to affect the relational-oriented exchange and outsourcing success.